AHP dan WP: Metode dalam Membangun Sistem Pendukung Keputusan (SPK) Karyawan Terbaik - Ahmad Gilang Ramadhan; Reva Ragam Santika (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
The best employee selection is an award given by the company to employees who can encourage all employees to improve their performance. However, for the assessment is usually still done subjectively and manually, and at least the support system in making decisions into this problem can be a problem. This study aims to build a decision support system in the selection of the best employees in accordance to the requirements specified by the company by using the Prototype model. Meanwhile, the method applies to test the consistency and accuracy of this system use the Analytical Hierarchy Process (AHP) and Weighted Product (WP). In selecting the best employees, there are several criteria to be assessed, namely: Knowledge, Ability, Attitude, Attendance, and Cooperation, as well as the number of subjects of this study consisting of five people. Our findings show that the accuracy rate of this system is below 10%, and the consistency index value is correct, so it can be used with a relative number of initial weights = 1. After testing or testing, the results obtained are all components or modules in this system already successfully and properly used as it should be.